THE BENEFITS OF SCHOOL FEEDING PROGRAMME IN WESTERN ZAMBIA - Sitali, Constance; Chakulimba, Oswell; Ng’andu, Sophie Kasonde (International Journal of Research -GRANTHAALAYAH, 2020)
The study sought to establish the benefits of school feeding programme (SFP) in Western Zambia. It also brought out the challenges encountered in the execution of the programme. This article is an extract from one of the objectives of ongoing study. School feeding entails the distribution of food commodities to children who attend school. The commodities may be locally grown and purchased or contributed by international donor community. The food may be consumed by the learners in school. In other settings, it may be given as take-home ration for consumption by the families that regularly send their children to school. The study employed a descriptive survey research design to collect, analyse and interpret both quantitative and qualitative data from 415 respondents. The results of the study showed that the school feeding programme is an intervention which has enormous education benefits; equitable access to education, increased school enrolment, improved attendance, punctuality and academic performance. Other benefits include: health and nutrition, social protection, parent involvement, and opportunities for local farmers. However, challenges were also reported; there were some possible negative attributes to the increase in the enrolment rates, that is, the educational quality may be compromised if the number of learners exceeds available resources such as desks, text books, teachers, and irregular supply of food to schools. The study recommended that plans and measures should be put in place by the government, relevant ministries and development partners on how to increase existing human, physical, and financial resources for the school feeding programme to be effective and sustainable. SFP should also be decentralized to the schools and community levels with more support from provincial offices to ensure a more effective school feeding programme.